Preliminary Outbreak Investigation and Spatial Epidemiology of Rabbit Hemorrhagic Disease Outbreak in Nigeria - Oyewo, Muftau; Al-Mustapha, Ahmad I.; Richards, Bukola A.; Abdulkareem, Lateefah; Olasoju, Taiwo; Babale, Sufiyan M.; Khalid, Hamza; Meseko, Clement; Balogun, Muhammad S. (Frontiers in Veterinary Science, 2022)
The outbreak of highly contagious transboundary rabbit hemorrhagic disease (RHD) in Nigeria has a severe socio-economic impact on the rabbit industry. We present the outbreak investigation and spatial epidemiology of the first confirmed RHD outbreak in Nigeria from a field survey of 28 stochastic outbreaks in Kwara State, north-central Nigeria. A total of 1,639 rabbits died from 2,053 susceptible rabbits. The serotype “RHDV-2” was detected in tissue samples from some of the outbreaks. The case fatality rate of the RHDV-2 outbreak was 79.8%. The source of the outbreak is still unknown. Most (71.4%) of the farmers had introduced new rabbits into their farms 1-2 weeks before the outbreak. Most of the farmers practiced biosecurity measures such as farm fencing (83.1%) and routine disinfection of the farm materials (53.6%). However, only 17.8% of the farmers enforced movement restrictions into their farms. Some of the farmers (42.8%) had restocked their farms after being affected by the RHD outbreak and 75% of all those farmers that have restocked had used the RHD vaccine. There was no statistically significant association between adherence to biosecurity measures and the RHD outbreak in affected farms (p = 0.408). However, the introduction of new rabbits into rabbit farms significantly pre-disposed farms to the RHD outbreak (p < 0.001). There is a need for active surveillance of RHD across the country to ensure efficient and effective tracking, monitoring, and control of the disease.